Design of Efficient Exciplex Emitters by Decreasing the Energy Gap Between the Local Excited Triplet (3LE) State of the Acceptor and the Charge Transfer (CT) States of the Exciplex - Wei, Xiaofang; Liu, Yanwei; Hu, Taiping; Li, Zhiyi; Liu, Jianjun; Wang, Ruifang; Gao, Honglei; Hu, Xiaoxiao; Liu, Guanhao; Wang, Pengfei; Lee, Chun-sing; Wang, Ying (Frontiers in Chemistry, 2019)
A series of thermally activated delayed fluorescence (TADF) exciplex based on the TX-TerPy were constructed. The electronic coupling between the triplet local excited states (3LE) of the donors and acceptor and the charge transfer states have a great influence on the triplet exciton harvesting and ΦPL. Herein, based on this strategy, three donor molecules TAPC, TCTA and m-MTDATA are selected. The local triplet excited state (3LE) of the three donors are 2.93, 2.72 and 2.52 eV in pure films. And the 3LE of TX-TerPy is 2.69 eV in polystyrene film. The energy gap between the singlet charge transfer (1CT) states of TAPC:TX-TerPy (7:1), TCTA:TX-TerPy (7:1) and the 3LE of TX-TerPy are 0.30 eV and 0.20 eV. Finally, the ΦPL of TAPC:TX-TerPy (7:1) and TCTA:TX-TerPy (7:1) are 65.2 and 69.6%. When we changed the doping concentration of the exciplex from 15% to 50%, the ratio of the triplet decreased, and ΦPL decreased to the half, perhaps due to the increased energy gap between 1CT and 3LE. So optimizing the 1CT, 3CT and 3LE facilitated the efficient exciplex TADF molecules.